Evaluation of determinants influence for consumption of livestock products in second-tier cities of Tamil Nadu in India - Priyadharsini, S; Kathiravan, G; Thirunavukkarasu, M; Ganpat, W (Bangladesh Journal of Animal Science, 2017)
A study was carried out in two Second-Tier cities of Tamil Nadu, viz., Coimbatore and Salem, with the objectives to analyze the factors influencing the consumption pattern of three major livestock products, namely milk, egg and meat. Multistage sampling procedure was adopted to select 160 household consumers, 80 from each of the cities. Relevant data were collected through personal interview with the help of a pilot-tested interview schedule. Semi-log functional analysis for household consumption of milk revealed that family size, education, region of sample household and dummies for children, income and physical exertion were found to be significantly influencing the consumption of milk. However, egg consumption was influenced by family size, education, food habits, region, presence of children/aged in the household, income levels and physical exertion of family members. Of the independent factors chosen for the model fitted for household meat consumption, family size and dummies for Hindu, region, aged and income categories were found significantly influencing the consumption of meat.As the consumers are segmented by the key quality attributes of livestock products and by socio-economic factors, strategies are necessarily to be evolved and strengthened for enabling niche marketing on identifiable sub-groups. Bang. J. Anim. Sci. 2016. 45 (3): 25-30